KHIND: hair dryer / Muhammad Haikal Muhammad Johan - Muhammad Johan, Muhammad Haikal (2022)
This case study will elaborate on the introduction to the company that is selected to study the complexities in business sector of home appliances products, which is KHIND. The issues and problem statement of current products, specifically hair dryer will also be stated in the case study. And finally, the expectation of the future of the product will also be discussed thoroughly. Based on the issues and problems stated, a careful findings and discussion will be made in the case study. We are also required to provide alternative solutions to the problems stated in the earlier phase of understanding the complexities of conduction business of home appliances products and services.